Utilization of Hand- Powered Corn Sheller: A Boon to Farmers/Corn Growers - Sillero, Ulysses S.; Sillero, Elena J. (JPAIR Multidisciplinary Research, 2009)
This technical study deals with the design, construction and test the usefulness and effectiveness of the improvised hand-powered corn sheller. The output of this study is purposely designed to help solve the predicament of the farmers most particularly the corn growers during power interruptions. The significant findings of the study revealed that the device is very useful and effective in shelling any size of corn minus electricity or gas. Aside from being economical, this device can be made using only scrap or junk materials that are locally available and can be found anywhere. It is also handy and can be operated anytime and anywhere the user wants it to be. The only limitation of the device is that, the output in shelling corn varies depending upon the speed and strength of the user. In terms of maintenance, the bearings need only to be oiled or greased anytime or the need arises to prevent rust. Further, the said device can promote a healthy exercise to the users, thus, shedding the users' unwanted cholesterols.
Keywords: hand-powered corn sheller; utilization; farmers; corn growers